ASYMMETRIC WARFARE AND THE CHALLENGES TO INTERNATIONAL HUMANITARIAN LAW - Aristoteles H Lawitang; Indra Laksamana, Tarsisius Susilo, Budiman Marpaung, Budi Saroso (JOURNAL OF LAW AND NATION, 2025)
In recent decades, asymmetric warfare has increasingly defined the landscape of armed conflict, largely due to the significant role played by non-state entities and their reliance on irregular strategies that strain the normative framework of International Humanitarian Law (IHL) (Kaldor, 2012; Hoffman, 2007). This article explores the misalignment between IHL’s core principles— such as distinction, proportionality, combatant status, and accountability—and the operational realities of asymmetric battlefields. A comparative analysis is conducted across three case studies: the Coalition’s operations against ISIS in Mosul, Myanmar’s military conflict with the Rohingya population, and Turkey’s intervention against the YPG in northern Syria. Findings reveal a structural gap in the legal responsibility between state and non-state actors, compounded by the limited enforcement mechanisms of IHL in non-international armed conflicts. The article proposes reform of international legal frameworks, the modernization of military doctrines and rules of engagement, and the integration of ethical and legal education into military training. These measures aim to maintain the relevance and effectiveness of IHL in facing future hybrid and asymmetric conflicts.